The impact of food reviewers on purchase intention in the food and beverage industry: the mediating role of user interaction - Vo Minh Sang; Bui Duy Khuong; Ly Yen Nhi; Luong Gia Han; Thach Minh Giau; Nguyen Thi Tuyet Ngoan (Cogent Business & Management, 2024)
This study examines the influence of food reviewers on user engagement and purchase intention in the food and beverage (F&B) sector. Findings indicate that food reviewers positively impact both user interaction and purchase intention, with three key factors emerging: reviewer reputation, video content, and video quality. However, the reviewers' expertise showed no significant effect on engagement or purchase intention. User engagement was also found to mediate the relationship between food reviewers and purchase intention, underscoring connections within the value chain linking food reviewers, user engagement, and purchase intention. The study provides theoretical insights by offering a framework to assess how TikTok food reviews affect young Vietnamese consumers' engagement and purchasing behaviors. It highlights user interaction's mediating role between food review components and purchase intention and supports the relevance of affiliate marketing theory in the F&B industry. Practical implications include strategies to enhance brand visibility through affiliate marketing with food reviewers and implementing food reviewer‑driven marketing communication initiatives tailored for the F&B sector.
Keywords: 650; affiliate marketing; food reviewer; user interaction; purchase intention; food and beverage